ASPECTOS BOTÂNICOS E MEDICINAIS DE Hygrophila R.Br. (ACANTHACEAE) DE OCORRÊNCIA NO CERRADO (CIPEEX, 2025)
The Acanthaceae comprise approximately 4,900 species and 190 genera, predominantly herbaceous to subshrub. Objective: This study describes the morphology of Hygrophila found in the Experimental Unit – UniEVANGÉLICA, Anápolis, and conducts a literature review on the medicinal potential of different species of this genus, aiming to contribute to the pharmacognostic knowledge of the group. Methods: Specimens of Hygrophila were collected and analyzed. The morphology of the plants was described in detail, following established taxonomic criteria for the genus. In parallel, a comprehensive bibliographic review was conducted on the medicinal action of different Hygrophila species, focusing on phytochemical studies and biological activities reported in the literature. Results: Morphological analysis of the specimens confirmed the identification of the species found and highlighted their distinctive features. The literature review revealed vast medicinal potential for Hygrophila species, with numerous studies reporting biological activities (antimicrobial, anti-inflammatory, antitumor, and antioxidant). The secondary metabolites most frequently found in Hygrophila species include terpenoids, alkaloids, and flavonoids, which are responsible for many of the pharmacological activities described. Conclusion: The study demonstrated the importance of Hygrophila species from both botanical and pharmacological perspectives. The detailed morphological description contributes to the identification and classification of species, while the literature review on medicinal potential highlights the relevance of these plants for the development of new drugs. The results obtained reinforce the need to deepen studies on the genus Hygrophila, particularly regarding its chemical biodiversity and therapeutic applications.
Keywords: Hygrophila; Acanthaceae; Taxonomy; Phytochemistry